The chemical composition of cassava leaves and root tissues (peel and parenchyma) - Gómez G., Guillermo G.; Valdivieso Garcia, Mauricio A.; Noma, AT (International Center for Tropical Agriculture, 1983)
The chemical composition, including the proximal composition, starch, sugar, amino acid and cyanide contents of leaves, root peel and parenchyuma of four (one local and three promising) cassava cultivars at four plant ages (6, 8, 10 and 12 months) is presented. The local cultivar showed lower leaf and root parenchyma DM contents, lower crude fiber and crude protein levels in root peel, a higher sugar content and lower cyanide concentration in root tissues, than the three promising cultivars. Most of the parameter studied were affected by the cultivar as well as by plant age. Less variability was observed for all criteria in the root parenchyma than in the leaves and root peel. The sulfur-containing amino acids were rather low in the cassava tissues analyzed and a high concentration of arginine was found in the root tissue samples. The cyanide concentration of root parenchyma was less variable than that of leaves and root peel; cv. M Col 1684 showed a higher cyanide content in the parenchyma (900 to 1000 mg/kg DM) than the other three cultivars, which ranged from 100 to 200 mg/kg DM. The local cultivar was the only one on which the cyanide content of leaves was higher thant that of the root peel. The hybrid CM 342-170 produced roots with the highest DM and starch contents.